Development of Auditing Compliance by Implementation of Blockchain Technology: An Explanatory Study based on Observations - Raju, Valliappan; Poh Phung, Siew (International Journal of Psychosocial Rehabilitation, 2020)
Blockchain is a generally new innovation shaking up the reviewing and confirmation calling. Some case the advantages got from blockchain will render the calling out of date. While far reaching selection of blockchain may make a few elements of examiners outdated, it will, in fact, open numerous entryways. This paper is an explanation of how blockchain technology can thrive to improve and stabilize Auditing services. It also includes Assurance sector. There has been no data collection, however, researchers took efforts to study the entire implementation strategies of Blockchain technology in Auditing and Assurance sector.